Tigridia pugana (Iridaceae: Tigridieae), a new species from Jalisco, Mexico - Rodríguez, Aarón; Ortiz-Catedral, Luis (Instituto de Ecología, A.C., 2006)
Tigridia pugana (Iridaceae: Tigridieae) is described as a new species. It is characterized by producing bulbils in the axils of the cauline leaves. The flower of Tigridia pugana resembles that of T. pulchella B.L. Rob. but differs by having longer style branches that are bifid their full length, longer inner tepals and shorter ovary and fruit. So far, the new species is known only from the Sierra de La Campana and Sierra de Manantlán, in the state of Jalisco, Mexico.